2016
DOI: 10.1039/c6ra15844g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static magnetic field on the performances of and anode biofilms in microbial fuel cells

Abstract: The electricity production and substrate removal rate of microbial fuel cells (MFCs) could be improved by the application of a static magnetic field (SMF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Architectural design of the MFC setup [112] Alternative electrode material selection [113] Improvement of the cathodes (viable alternatives to platinum) [114] Closer-spaced electrodes (leading to a decrease in ohmic resistance) [115] Solution selection (allowing for increased conductivity) [116] Addition of substrates (more acquiescent to energy production) [21] Enhancement of appropriate fuel source [117,118] Introduction of a magnetic field to MFC configurations [119,120] The introduction of a magnetic field to living microorganisms produces a phenomenon known as the magnetic biological effect [121]. This effect has been shown to induce a series of biological reactions in microorganisms, for example, magnetic fields effect DNA, enzymes and organisational structure of biofilms, which in turn can lead to an alteration in the metabolism of the microorganism [122,123].…”
Section: Mechanism Refmentioning
confidence: 99%
“…Architectural design of the MFC setup [112] Alternative electrode material selection [113] Improvement of the cathodes (viable alternatives to platinum) [114] Closer-spaced electrodes (leading to a decrease in ohmic resistance) [115] Solution selection (allowing for increased conductivity) [116] Addition of substrates (more acquiescent to energy production) [21] Enhancement of appropriate fuel source [117,118] Introduction of a magnetic field to MFC configurations [119,120] The introduction of a magnetic field to living microorganisms produces a phenomenon known as the magnetic biological effect [121]. This effect has been shown to induce a series of biological reactions in microorganisms, for example, magnetic fields effect DNA, enzymes and organisational structure of biofilms, which in turn can lead to an alteration in the metabolism of the microorganism [122,123].…”
Section: Mechanism Refmentioning
confidence: 99%
“…In Zhao et al (2016), the use of a magnetic field of 220 mT stimulated the activity of the biofilm at the anode of a fuel cell for treating wastewater, thanks to the production of more extracellular polymeric substance. With a magnetostatic field of 360 mT, instead, the opposite occurred due to harmful effects to microbial growth.…”
Section: Studies In An Environmental Settingmentioning
confidence: 99%
“…86 In a BES, this process may affect the activity of enzymes and the bioelectrochemical activity or biomass of biolms and thus exert an inuence on the organizational structure of microorganisms. [87][88][89] Studies have indicated that a static magnetic eld promoted the synthesis of dehydrogenase and lipid peroxidation, exerting a positive effect on the degradation of organic matter. 90,91 The occurrence of this effect may be attributed to the promotion of electron transfer on the anode surface in a static magnetic eld, thus adjusting the biocatalysis and conversion of electrode-related enzyme assembly.…”
Section: Magnetic Eldmentioning
confidence: 99%
“…Under the stimulation of a static magnetic eld, the microbial community can also produce more extracellular polymers that allow the microorganisms to resist unfavourable environmental conditions and improve the stability of the biolm structure. 88 In addition, the magnetic eld may also affect the internal resistance of the BES and the electroactive matter on the electrode surface. In a study of the inuence of a magnetic eld on the performance of an MFC, the MFC had a stronger ability to produce electricity and a smaller apparent internal resistance under a magnetic eld of 200 mT than the blank control group, and the electroactive substances on the surface of the electrode increased, thereby decreasing the electrode activation resistance.…”
Section: Magnetic Eldmentioning
confidence: 99%
See 1 more Smart Citation